(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: Carcinoma pancreas is being diagnosed increasingly with the help of conventional imaging like ultrasonography (USG), computerized tomography (CT) scan and magnetic resonance imaging (MRI).Imaging also gives the opportunity to assess resectability. In our country MRI and CT scan are not widely available and most of the pancreatic carcinoma is too advanced for curative surgical resection when diagnosed. These are unresectable carcinoma pancreas (UCP). Objectives: To evaluate the efficacy of imaging in diagnosing carcinoma pancreas and to assess resectability after comparing them with peroperative findings. Methods: This retrospective study was carried out in the department of Hepato-Biliary-Pancreatic Surgery in Bangladesh Institute for Research and Rehabilitation in Diabetic Endocrine and Metabolic disorders (BIRDEM) hospital, Dhaka, Bangladesh from July 2004 to June 2006 (2 years). After laparotomy findings and histopathological confirmation 50 patients were labeled as UCP. Among 50 patients male were 28 & female patients were 22. Imaging modalities used before surgery was assessed and compared with per operative findings. USG were done in all patients and CTscan in 45 patients. MRI was done in 08 patients suspected clinically as pancreatic carcinoma where USG /CT scan had failed to reach a conclusion. Findings of the various imaging studies regarding diagnosis and unresectability were compared with per operative findings. Results: USG was able to diagnose 42 (84%) pancreatic carcinoma patients with unresectibility in 29 (69%). Forty five patients (90%) were diagnosed by CT scan and could label 38 (84.44%) as unresectable. MRI was 100% accurate to diagnose and label the entire 08 patient as unresectable carcinoma pancreas. Cumulative multimodal preoperative imaging was 91.33% accurate in diagnosing carcinoma pancreas and could tell the features of unresectibility in 73.59% patients. Conclusion: CT scan should be the primary imaging modality for diagnosing pancreatic carcinoma and its resectability. MRI is very promising for diagnosing and assessing UCP. Multimodal imaging is better than single imaging. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 23-26